Progress on the Fifteenth General Review of Quotas-Report of the Executive Board to the Board of Governors (October 2017). (Policy Papers; Policy Paper ;, 2021)
Following the guidance on the Board of Governors Resolution No. 72-1 (December 2016), on October 4, 2017, the Executive Board discussed and adopted its first semi-annual report on progress on the Fifteenth Review. The report covered issues related to the quota formula and realigning quota shares as well as issues related to the adequacy of Fund resources, discussed in informal meetings on September 1 and on September 15, 2017, respectively.